Global Burden of Orofacial Clefts and the World Surgical Workforce. Issue 4 (October 2021) - Massenburg, Benjamin B.; Hopper, Richard A.; Crowe, Christopher S.; Morrison, Shane D.; Alonso, Nivaldo; Calis, Mert; Donkor, Peter; Kreshanti, Prasetyanugraheni; Yuan, Jie
Abstract : Background: Orofacial clefts are one of the most common congenital anomalies, but this disease burden is unevenly distributed worldwide. The authors hypothesize that this burden falls disproportionately on the countries with the smallest surgical workforce or lowest Socio-Demographic Index, rather than those with the highest prevalence of disease. Methods: The authors estimated the prevalence and disease burden of orofacial clefting from 1990 to 2017 in 195 countries using the Global Burden of Disease methodology. Prevalence and disability-adjusted life-years were compared geographically, temporally, and against the size of the national surgical workforce, Socio-Demographic Index, and income status. Linear and logarithmic regressions were performed. Results: In 2017, the prevalence of orofacial clefting was estimated to be 10.8 million people, representing a disease burden of 652, 084 disability-adjusted life-years, with most of this disease burden experienced by low- and middle-income countries (94.1%). From 1990 to 2017, there was a decrease in disease burden (-70.2%) and prevalence (-4.9%). There was negative logarithmic association between surgical workforce size and disease burden, with a surgical workforce of greater than six providers per 100, 000 population (3.6 disability-adjusted life-years versus 22.4 disability-adjusted life-years per 100, 000 population; p < 0.0001). Conclusions: Burden of orofacial clefting has a strong negative association with the size of the surgical workforce, suggesting that strengthening the surgical workforce will help alleviate this burden. Epidemiologic data on countries and regions with inadequate surgical workforces and high disease burden should guide future research efforts and allocation of resources, and guide the treatment and educational goals of international charitable organizations.